Waqf laws and management - Rashid, Syed Khalid (Genuine Publications & Media Pvt. Ltd., 2012)
The book deals with effective utilization of waqf properties and their resources through better laws and management technques. Discussion is with reference to such countries like Malaysia, Bosnia, and Nigeria about which it is not easy to find material. In case of Malaysia the waqf laws of three states-Selangor, Malaka and Negri Sembilan-has been appended in the book to provide valuable material for comparative studies.